Accelerations - a new approach to quantify physical performance decline in male elite soccer? - Dalen, T.; Lorås, H.; Håvard Hjelde, G.; Naess Kjøsnes, T.; Wisløff, U. (European Journal of Sport Science, 2019)
The aim of the current study was (1) to investigate whether the number of accelerations is a more precise estimate of performance decline in soccer compared to distances with high-speed running (HSR) and (2) to compare changes in the number of accelerations and HSR distances across playing positions in order to examine whether the match profiles of the physical measures are consistent or demonstrate high interposition variability. The dataset includes domestic home games (N?=?34) over three full seasons (2012-2014) for a team in the Norwegian Elite League. The change in the number of accelerations throughout the match demonstrates a more clear pattern compared to the distance covered by HSR. In numbers of accelerations, a systematic and linear decrease can be observed throughout the match, with 34% less accelerations from the first to the last 5-minute period of the game (6.7 vs. 4.4 accelerations). This pattern of results captures the change in the number of accelerations across all positions. HSR distance had more variability during the match. All five positions investigated displayed a similar trend in accelerations and HSR profiles after the peak periods in each half. In contrast to the absolute number of accelerations, there were major positional differences in the mean HSR distance during the match. Our data suggest a more visible performance decline in the number of accelerations from the start to the end of the game, than the decline in the distance covered by HSR distance.